2022
DOI: 10.20473/vol9iss20222pp140-155
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Diversifikasi Pembiayaan Sektoral terhadap Non-Performing Financing Bank Pembiayaan Rakyat Syariah

Abstract: ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh diversifikasi pembiayaan dengan beberapa kontrol variabel baik variabel internal bank maupun variabel eksternal terhadap NPF BPRS di Indonesia. Faktor internal terdiri dari aset, CAR, pembiayaan, efisiensi operasi, sedangkan variabel eksternal adalah kondisi ekonomi makro yaitu output domestik dan tingkat inflasi. Penelitian ini menggunakan data time series, bulan Januari 2010 sampai Desember 2019. Penelitian ini menggunakan metode Autoregressive Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These results are consistent with research conducted by Adzobu, et al (2017) that diversification of the financing portfolio alone does not guarantee improved performance and reduced risks to banks. Furthermore, research conducted by Aiyubbi, et al (2022) found that diversification led to an increase in problem financing at BPRS in Indonesia. The reason for this may be that concentrating the financing portfolio increases monitoring efficiency, as banks may have expertise in the sector they are lending to.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with research conducted by Adzobu, et al (2017) that diversification of the financing portfolio alone does not guarantee improved performance and reduced risks to banks. Furthermore, research conducted by Aiyubbi, et al (2022) found that diversification led to an increase in problem financing at BPRS in Indonesia. The reason for this may be that concentrating the financing portfolio increases monitoring efficiency, as banks may have expertise in the sector they are lending to.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the economic turmoil, if banking stability is in good health, banks can carry out activities and also collect and distribute funds and intermediation functions properly (Dutta & Saha, 2021). Banking stability describes a balanced and stable condition in a banking institution (Aiyubbi et al, 2022). Banking stability is one part of financial system stability, which functions to allocate funds from those who experience a surplus to those who experience a deficit.…”
Section: Literature Review Banking Stabilitymentioning
confidence: 99%
“…The ratio used in measuring non-performing financing using Non-Performing Financing (NPF). NPF is the ratio between financing that has doubtful and bad quality and the total financing provided to the community (Aiyubbi et al, 2022). The possibility of losses to funding made by banks.…”
Section: Risk Of Financingmentioning
confidence: 99%